The celebrated comic duett in the opera of Cinderella : autograph manuscript - Rossini, Gioacchino, 1792-1868 (Tufts University Tisch Library, 2025)
Asa Tufts Collection number: 23.MMeT; Provenance: From the Asa A. Tufts Collection, Tufts University Special Collections.